The rheology of colloidal and noncolloidal food dispersions - Genovese, Diego Bautista (2007)
Rheological data on a food together with data on its composition and structure or microstructure should lead to understanding the interrelationships between them. A number of foods are dispersions of solids in liquids, liquids in liquids, or gas in liquids. The dispersed particles may be colloidal in nature with dimensions < 10 μm, or larger noncolloidal particles (> 10 μm). For both colloidal and noncolloidal dispersions (either in dilute or concentrated regimes), several theoretical equations exist that provide insights into the role of key rheological parameters, such as particle volume fraction and size, interparticle forces, and fractal dimension on their viscosity, yield stress, and modulus. When theoretical models cannot be easily applied to foods with complex structures, structural analysis and structure-based models provide insight into the role of solids loading and interparticle bonding on rheological behavior. In this review, recent studies on colloidal and noncolloidal food dispersions in which theoretical models as well as structural analysis were employed are discussed.